Summer Activity Sensor Data from Collars Deployed on Female Polar Bears in the Chukchi Sea 1989 to 1995 and Southern Beaufort Sea 1989 to 2014 - USGS Alaska Science Center, Polar Bear Research Program (USGS Science Data Catalog, 2017)
These are data collected from two types of activity sensors housed within collars deployed on female polar bears in the Chukchi and southern Beaufort Seas during the months of July through October between 1989 and 2014. Mercury tip-switches were deployed 1989 to 2009 and accelerometers were deployed 2009-2014. Activity sensor readings were related to habitats used by polar bears as described in the methods below.